Dampak Pengaruh Promosi Rokok Elektrik Terhadap Minat Konsumen Generasi Z Di Sukawinatan - Maulana, Adra Fikri; Abiyyu, M. Nibras; Razzaq, Abdur; Nugraha, Muhamad Yudhistira (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
The purpose of this study is to investigate the influence of e-cigarette promotion on Gen Z consumers in Sukawinatan. E-cigarette promotion on Gen Z consumers in Sukawinatan. This study uses a qualitative approach to investigate Generation Z’s perceptions, experiences, and motivations, promoting popular electronic products on various media platforms. Generation Z’s experiences and motivations in promoting popular electronic products on various media platforms. Through participant observation and analysis, this study learns to explain how promotional strategies, such as using influencers, visually appealing content, and focusing on lifestyle choices, influence consumer preferences and electronic consumption among Generation Z. Explaining how promotional strategies, such as using influencers, visually appealing content, and focusing on lifestyle choices, influence consumer preferences for electronic consumption among Generation Z. According to the results of the study, e-cigarette promotion not only affects men’s desire to buy, but also shapes their perception of it as a modern, trendy, and safe electric product. Promotion not only affects men’s desire to buy, but also shapes their perception of the product as a modern, trendy, and safe product. In addition, this study studies to identify the role of social media and brave communities in disseminating information and fostering positive electronic culture in Generation Z. Identifying the role of social media and brave communities in disseminating information and fostering positive electronic culture in Generation Z. The study provides important information on how changes in electrical power and its implications affect public health, especially among the younger generation. Changes in electrical power and its implications affect public health, especially among the younger generation.